Pengaruh Pelatihan Pemasaran Digital Terhadap Kinerja UMKM di Masa Pandemi Covid - Marjukah, Anis (Jurnal Keuangan dan Bisnis, 2022)
Research objective to analyze the role of digital training in improving the performance of MSMEs during the Covid-19 pandemic. The history of the Indonesian economy, MSMEs, is a strengthening of the nation's economy. The Covid-19 pandemic storm, requires MSME actors to transform into the digital era in order to maintain resilience and improve their performance. Strengthening MSMEs with digital marketing training needs the government and other stakeholders. MSME actors in DIY, participants in digital marketing training are the population in this study. Sampling technique: simple random sampling, a total of 112 selected samples. SEM approach, with data processing supported by the LISREL program was used as an analytical tool.Finding that digital marketing training has a positive and significant impact on improving the performance of MSMEs.Theoretical implications provide an explanation of the role of digital marketing training in improving the performance of MSMEs. Practical implications: to improve performance, MSME actors need to implement digital marketing, starting with digital marketing training. Key words: Digital Marketing; MSME’s Performace; Training.